(untitled) (Docentes 2.0 Journal, 2026)
Research in the 21st century was challenged by the need to transcend reductionist paradigms that constrained the understanding of complex, dynamic, and interconnected educational realities. In response, this essay proposed a transcomplex architecture of networked learning as an integrative epistemological framework to re-signify knowledge construction in emerging educational and technological environments. The study was framed within an inductive method, under a humanistic paradigm, with a qualitative interpretative approach, descriptive-interpretative type, and a topical narrative design. Methodologically, it was grounded in a critical and interpretative documentary review of scientific literature indexed in high-impact academic databases, which was analyzed through thematic and hermeneutic techniques. The analysis addressed the transition from disciplinary fragmentation to relational rationality, reconceptualized learning as an emergent phenomenon within interconnected ecosystems, examined the reconfiguration of expert knowledge in contemporary professional dynamics, and explored the constitutive role of technological mediations in hybrid learning environments. These dimensions were articulated into a transcomplex analytical framework that integrated epistemological, pedagogical, and technological perspectives. The study contributed a transcomplex conceptual model, hereafter referred to as the transcomplex architecture of networked learning, which redefined knowledge construction as a relational, distributed, and technologically mediated process. The findings positioned transcomplexity as a robust epistemological foundation for understanding and transforming educational realities, emphasizing dialogicity, interdisciplinarity, and the co-construction of knowledge in contexts shaped by uncertainty, interconnectivity, and digital mediation.